A CASE OF NECROSIS TYPE ISCHEMIC ENTERITIS - HASEGAWA, Yasuhiro; TAKEMURA, Shinichi; KIKUCHI, Jun (Nihon Rinsho Geka Gakkai Zasshi (Journal of Japan Surgical Association), 2006)
A 44-year-old man who had been medicated for hypertension since January 2002 had intermittent abdominal pain on August 15, 2004. He was referred to the hospital on August 19, because the intermittent gastric pain persisted despite medical treatment at another hospital. Conservative therapy resulted in a decrease of frequency of episodes of abdominal pain. However, on August 23, intermittent pain became severe. Multiple deposits of small intestinal gas were present on abdominal X-ray, and ascites and extremely edematous change of the ileum were seen on abdominal CT scan. So emergency operation was performed. At operation, we found about 40cm long ischemic or necrotic change of the ileum and partially resected the changed ileum. The histopathological diagnosis was necrosis type ischemic enteritis. The patient's postoperative course was uneventful. He was discharged from the hospital 17 days after the oppration. Ischemic enteritis of the small intestine is relatively rare and we often have difficulties in preoperative diagnosis. In this case, we could diagnose the disease after the operation.